The Aesthetics Of War: “the End” And “the Ride Of The Valkyries” In Apocalypse Now (1979) By Francis Ford Coppola - Terki Nassima (University of Eloued جامعة الوادي, 2025)
This article considers the way music and sound is integrated in Francis Ford Coppola’s Apocalypse Now (1979) through “The Ride of the Valkyries” (1856) by Richard Wagner and “The End” by The Doors (1967). It is a study of sound and music through the screen that refers mainly to Alvaro Barbosa and Kristine Dizon through their article “The Film Sound Analysis Framework: A conceptual Tool to interpret the Cinematic Experience” (2020). Putting together sound and image, the analysis reveals that Coppola uses sound, rock and classical, to blur boundaries between beauty and the brutality of the Imperial ideology, transforming warfare into a surreal aestheticized spectacle that implicates audiences in the seductive madness of violence.
Article . Ex Professo. Vol. 10. N.2
Keywords: Appcalypse Now; The Doors; Sound; War; Wagner